Pengenalan Kebudayaan Bengkulu melalui Rancang Bangun SIPEDALU - Nurul Renaningtias; Julia Purnama Sari (JSAI (Journal Scientific and Applied Informatics), 2024)
The presence of technology plays an important role in all sectors of life, one of which is the culture and tourism sector. The culture and tourism sector is a sector that has great potential in the development of a region, so special attention needs to be paid to encourage development and progress in this sector, especially culture and tourism in Bengkulu. Bengkulu has a variety of culture and tourism, both natural tourism, cultural tourism and historical tourism which have their own special features and uniqueness that must be developed and preserved. However, until now, information about culture and tourism in Bengkulu Province has not been well published. There are still many tourists and people who do not know about the diversity of culture and tourism in Bengkulu Province. So a new innovation is needed by utilizing web-based technology by building an information system for introducing Bengkulu culture called SIPEDALU. The method used in developing this system is the Waterfall method. The results of this research are an information system for introducing culture and tourism in Bengkulu Province.